Theory and simulation of molecular interactions in biological systems - Karunaweera, Sadish (Kansas State University, 2017)
The impact of computer simulations has become quite significant especially with the development of supercomputers during the last couple of decades. They are used in a wide range of purposes such as exploring experimentally inaccessible phenomena and providing an alternative when experiments are expensive, dangerous, time consuming, difficult and controversial. In terms of applications in biological systems molecular modeling techniques can be used in rational drug design, predicting structures of proteins and circumstances where the atomic level descriptions provided by them are valuable for the understanding of the systems of interest. Hence, the potential of computer simulations of biomolecular systems is undeniable. Irrespective of the promising uses of computer simulations, it cannot be guaranteed that the results will be realistic. The precision of a molecular simulation depends on the degree of sampling achieved during the simulation while the accuracy of the results depends on the satisfactory description of intramolecular and intermolecular interactions in the system, i.e. the force field. Recently, we have been developing a force field for molecular dynamics simulations of biological systems based on the Kirkwood Buff (KB) theory of solutions, not only with an emphasis on the accurate description of intermolecular interactions, but also by reproducing several physical properties such as partial molar volume, compressibility and composition dependent chemical potential derivatives to match with respective experimental values. In this approach simulation results in terms of KB integrals can be directly compared with experimental data through a KB analysis of the solution properties and therefore it provides a simple and clear method to test the capability of the KB derived force field. Initially, we have provided a rigorous framework for the analysis of experimental and simulation data concerning open and closed multicomponent systems using the KB theory of solutions. The results are illustrated using computer simulations for various concentrations of the solutes Gly, Gly₂ and Gly₃ in both open and closed systems, and in the absence or presence of NaCl as a cosolvent. Then, we have attempted to quantify the interactions between amino acids in aqueous solutions using the KB theory of solutions. The results are illustrated using computer simulations for various concentrations of the twenty zwitterionic amino acids at ambient temperature and pressure. Next, several amino acids were also studied at higher temperatures and pressures and the results are discussed in terms of the preferential (solute over solvent) interactions between the amino acids. Finally, we have described our most recent efforts towards a complete force field for peptides and proteins. The results are illustrated using molecular dynamics simulations of several tripeptides, selected peptides and selected globular proteins at ambient temperature and pressure followed by replica exchange molecular dynamics simulations of a few selected peptides.
Keywords: Computer simulation; Molecular dynamics; Force field; Kirkwood-Buff theory; Amino acids